PANDANGAN ULAMA BALANGAN TENTANG PENGELOLAAN SUMBER DAYA ALAM BATUBARA DI BALANGAN DALAM PERSPEKTIF EKO-SUFISME - Assya’bani, Ridhatullah; Syadzali, Ahmad (Faculty of Ushuluddin and Humanities, 2014)
It starts from a consciousness that how importance of the role of scholars in their assessments and views onsocial reality, particularly on the issue of environmental crisis that occurred to the people in Balangan regency. Based on the research, the writers found a classification of the scholarsâ views on coal mining and natural resources exploitation and the environmental impacts and social impact as the result. The first view, they agree fully to coal mining activities. Second view, they disagree on coal mining activity. The third view, the scholars who do not give a clear view or grey view to coal mining activities. Based the analysis conducted by the writers by using the eco-sufism concepts as theoretical basis, the writers concluded that their views who disagree with coal mining activity is based on the view of environmental ethics in accordance with the concept of eco-sufism.